2012
DOI: 10.1098/rstb.2011.0122
|View full text |Cite
|
Sign up to set email alerts
|

A neuropsychological perspective on the link between language and praxis in modern humans

Abstract: 6University Claude Bernard Lyon 1, 43 boulevard du 11 novembre 1918, 69622 Villeurbanne, FranceHypotheses about the emergence of human cognitive abilities postulate strong evolutionary links between language and praxis, including the possibility that language was originally gestural. The present review considers functional and neuroanatomical links between language and praxis in brain-damaged patients with aphasia and/or apraxia. The neural systems supporting these functions are predominantly located in the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 163 publications
(268 reference statements)
1
21
0
Order By: Relevance
“…These may be informative of evolutionary divergences in the behavioural capacities of the chimpanzee and human lineages. Our behavioural results reviewed above can be seen as bridging the gap between work reviewed elsewhere in this issue on monkey tool use and social learning [85], and work on human tool use and on the evolution of increasing cognitive demands in hominin Palaeolithic stone tool traditions [86,87]. Such work does not directly address African ape -human cognitive and behavioural contrasts, nor do we yet have any brain imaging observations even for a human model of the circuits activated in a nutcracking as compared with a simple stone-flaking task (see also [88,89]).…”
Section: Brain Evolution In Humans and Chimpanzees: Issues Relevant Tmentioning
confidence: 97%
“…These may be informative of evolutionary divergences in the behavioural capacities of the chimpanzee and human lineages. Our behavioural results reviewed above can be seen as bridging the gap between work reviewed elsewhere in this issue on monkey tool use and social learning [85], and work on human tool use and on the evolution of increasing cognitive demands in hominin Palaeolithic stone tool traditions [86,87]. Such work does not directly address African ape -human cognitive and behavioural contrasts, nor do we yet have any brain imaging observations even for a human model of the circuits activated in a nutcracking as compared with a simple stone-flaking task (see also [88,89]).…”
Section: Brain Evolution In Humans and Chimpanzees: Issues Relevant Tmentioning
confidence: 97%
“…Many have suggested that the evolution of tool manufacture and use in humans had profound effects on a variety of complex cognitive functions such as language and speech, as well as increased brain size and complexity, including lateralization in structure and function in hand use [10][11][12][13][14][15][16]. Specifically, it has been hypothesized that the left hemisphere's specialization for praxic and speech functions evolved from adaptation in early hominids for tool manufacture and use [14,17,18]. In these evolutionary models, speech co-opted neural and biological systems involved in manual motor actions, such as prehensile grasping and tool use, with increasing selection for fine motor skill necessary for the articulation of speech in early humans, after the split from the common ancestor with chimpanzees.…”
Section: Introductionmentioning
confidence: 99%
“…In another study which looked at “pantomime” skills in people with aphasia, van Nispen and colleagues (2016) found that semantic deficits associated with aphasia also appear to have a negative impact on the kinesthetic representation of the distinctive features of objects 75 . In their 2012 review, Roby-Brami et al reported that brain areas which underlie the motion of reaching and grasping are connected with visual pathways as part of a “dynamic system” of networks which communicate via mirror neurons with Broca’s area 76 .…”
Section: A Motor-language Connection and Tdcsmentioning
confidence: 99%